An evaluation of ticagrelor for the treatment of sickle cell anemia. Issue 10 (2nd October 2020) - Ribeiro-Filho, Jaime; Yahouédéhou, Sètondji Cocou Modeste Alexandre; Pitanga, Thassila Nogueira; Santana, Sânzio Silva; Adorno, Elisângela Vitória; Barbosa, Cynara Gomes; Ferreira, Júnia Raquel Dutra; Pina, Eugênia Terra Granado; Neres, Joelma Santana dos Santos; Leite, Ivana Paula Ribeiro; Lyra, Isa Menezes; Goncalves, Marilda Souza
ABSTRACT: Introduction: Ticagrelor is an antiplatelet agent approved for the treatment of patients with an acute coronary syndrome or a history of myocardial infarction. Considering the evidence demonstrating that ticagrelor-mediated inhibition of platelet activation and aggregation have beneficial effects in the treatment of thrombotic conditions, clinical studies have been conducted to evaluate the use of this drug for the treatment of sickle cell disease (SCD), demonstrating satisfactory tolerability and safety. Areas covered: Clinical investigation has characterized the pharmacokinetic and pharmacodynamical profile, as well as the efficacy and safety of ticagrelor to prevent painful vaso-occlusive crisis (painful episodes and acute chest syndrome) in SCD patients. Expert opinion: While phase 1 and 2 clinical trials demonstrated satisfactory tolerability and safety, the conclusion of phase 3 clinical trials is crucial to prove the efficacy of ticagrelor as a therapeutic option for the treatment of SCD. Thus, it is expected that ticagrelor, especially in combination with other drugs, will improve the clinical profile and quality of life of patients with SCD.